THE EFFECT OF HYDROSULPHURIZATION ON STABLE CARBON ISOTOPIC COMPOSITIONS OF FREE AND SULPHUR-BOUND LIPIDS - Schouten S.; Sinninghe Damste J.S.; Kohnen M.E.L.; De Leeuw J.W. (My University, 1995)
1-Decene was subjected to hydrosulphurization under phase-transfer conditions at room temperature. Compound-specific isotope analysis revealed that 1-decene becomes enriched in 13C with increasing yields of sulphurization whilst the sulphur compounds formed are initially depleted in 13C compared to the starting substrate. The average carbon isotopic fractionation effect of the reaction on the two carbon atoms involved is ca. -20%%. Sedimentary sulphur compounds, however, do not show this fractionation effect indicating that either a different sulphurization reaction with different isotope effects has occurred or that functionalized lipids may have been fully sulphurized.